Testing the Environmental Kuznets Curve Hypothesis: An Empirical Study for Peru - Mougenot, Benoit; Durand Santa MarÃa, Rosa Pamela; Koc Olcese, Claudia Lucia (International Journal of Energy Economics and Policy, 2022)
This research analyzes the Peruvian engagement against climate change through the impact of the per capita income on the environmental pollution in the national scenario during the annual period of 1980-2019. For this, the logic of the Environmental Kuznets Curve will be used, in which an "inverted U" curve shape affirms that the economic growth is favorable for the environment in the long term because an optimal income point is reached and pollution begins to decline. For this analysis, the national exports are included as a third variable, and also is considered a cubic regression equation to the original Kuznets model. Through the estimation by Dickey-Fuller and Phillips-Perron unit root tests, Granger Causality Test, the Vector Autoregression Model (VAR) method and the Forecast Graphics, it is shown that, similar to other countries of the region, Peru is actually on the initial part of the curve, where income and pollution have a growing direct relation. Finally, the models that fitted the relationship of these variables were the original model and the model with exports included.